Strategi Pembelajaran Metodologi Penelitian Bahasa Arab di Era Pandemi - Luhuringbudi, Teguh (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This research paper aims to analyze innovative learning strategies for Arabic language research methodology in the pandemic era, which requires students to be able to write Student Article Plans (RAM) based on the offer of Selected Journal Article Titles (AJP) presented by the course lecturer. This research paper is a